A perturbation approach in determination of closed-loop optimal-fuzzy control policy for planetary landing mission - Afshari, H H; Roshanian, J; Novinzadeh, A B (Proceedings of the Institution of Mechanical Engineers. Part G, Journal of aerospace engineering, 2009)
Abstract Development of time-optimal strategy for non-linear problem of planetary landing mission by using perturbation technique is investigated on two scenarios in this study. The first scenario includes finding an optimal control policy for descent in the variable gravitational field of the target planet analytically. In the second scenario, the optimal policy is derived by considering the effect of spacecraft mass variations in an analytic solution. To validate the accuracy of each generated policy, a numeric method such as steepest descent is employed. Afterwards, the fuzzy algorithm is followed to achieve the closed-loop guidance strategy for this non-linear system. The training process of the fuzzy system is based on the achieved perturbation solution of variable mass landing problem by utilizing a set of states-related non-dimensional variables for faster convergence rate. Finally, the lunar landing mission is demonstrated as a viable example of the non-linear planetary landing mission. Simulation results show that the presented optimal guidance laws are so effective which can be utilized in the real world spacecraft applications.